Programming in BASIC - Lampton, Christopher. 4 0 16; 5 (New York : Watts, 1983)
Introduces the computer program language known as Basic, which was originally developed as a tool for teaching computer programming, but may also be used for writing extremely sophisticated programs.
Includes index.
Booklist
7.6;5-8;5-8
Keywords: 2 -- 0; 6; BASIC (Computer program language);Programming languages (Computers);Computers. -- 20; 20; 2